The Effect of Cell Surface Area on the Effectivity and Reusability of Bixin Sensitized Solar Cells - Anissa Bella Maharani; Lia Destiarti; Winda Rahmalia (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2022)
Dye-Sensitized Solar Cells or DSSC is the latest solar cell type generation that uses natural dyes as sensitizers. Bixin extracted from the seeds of kesumba (Bixa orellana L) is one of the natural dyes that can be used as a sensitizer. This study aims to determine the effect of the active surface area of solar cells on the effectivity and reusability of bixin-sensitized solar cells based on their open-circuit voltage (Voc), short-circuit current (Isc), and maximum energy conversion efficiency. The results of this study will provide an overview of the best surface area to produce DSSC with the highest maximum energy conversion efficiency and the lifetime of bixin sensitized solar cells. The measurement results showed that the resulting Voc for each variation of the surface area 1, 2, and 3 cm2 was 344; 719; 1002 mV under intensity 100 mW cm-2, while the Isc produced under the same intensity was 0.223; 0.471; 0.680 mA. Based on the calculation results, the maximum power generated by each surface area was 0,077; 0,338; 0,681 W. This means that the larger the active surface area of the solar cell, the greater the voltage and current generated. In this work, the highest efficiency was produced by solar cells with a surface area of 2 cm2, which is 0.085%. The solar cells fabricated in this study can be reused for five days under continuous irradiation.